1993
DOI: 10.1016/0016-7185(93)90011-6
|View full text |Cite
|
Sign up to set email alerts
|

Women's employment and peripheralisation: the case of Ireland's branch plant economy

Abstract: Abstract:The mobilisation of reserves of unskilled women workers played a key role in the new international division of labour which emerged in the 1960s and 1970s. This is illustrated in the case of the branch plant economy which emerged in the Republic of Ireland after 1960. There has been rapid growth in femaie employment in the electrical engineering sector'which is dominated by foreign firms. A case study of the eiectronics industry reveals strong gender segmentation and a heavy reliance on assembly work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
(1 reference statement)
0
12
1
Order By: Relevance
“…This fits earlier findings of a government survey, which found an almost even distribution of employment, with women accounting for 55% of the offshore service labour force (NATIONAL STATISTICS OFFICE, 2010). This stands in contrast to earlier findings that branch plants significantly prefer to hire female labour (TOWNROE, 1975;BREATHNACH, 1993;BREATHNACH, 2000).…”
Section: External Decision-making and Controlcontrasting
confidence: 86%
See 2 more Smart Citations
“…This fits earlier findings of a government survey, which found an almost even distribution of employment, with women accounting for 55% of the offshore service labour force (NATIONAL STATISTICS OFFICE, 2010). This stands in contrast to earlier findings that branch plants significantly prefer to hire female labour (TOWNROE, 1975;BREATHNACH, 1993;BREATHNACH, 2000).…”
Section: External Decision-making and Controlcontrasting
confidence: 86%
“…Considerable attention has been devoted to the role of multinational companies and their impact on regional development in the places where they invest (DUNNING and LUNDAN, 2008;DICKEN, 2011). Starting from the 1970s, the literature on regional development has been occupied with investment flows between industrialized countries, with a predominance of studies focusing on peripheral regions in the UK and Ireland, which found evidence of branch-plant economy symptoms (FIRN, 1975;TOWNROE, 1975;HOOD and YOUNG, 1976;PHELPS, 1993;BREATHNACH, 1993;PIKE, 1998). The so-called 'branch-plant syndrome' is the result of a concentration of fully owned subsidiaries (branch plants) of larger companies in specific regions, which are characterized by external ownership and control, and truncated development opportunities.…”
Section: Towards a Framework Assessing Economic Development And Depenmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers in offshore back of ces are, for the most part, young, exible and female (Wilson 1995), mainly as a consequence of socialization and gender stereotyping processes that steer mostly women towards this type of work. The resulting gender segmentation in turn facilitates the utilization of social control processes similar to those which apply to female-intensive manufacturing operations (Breathnach 1993).…”
Section: T H E I N T E R N a T I O N A L D I V I S I O N O F L A B O mentioning
confidence: 99%
“…The main attractions offered to inward investors have been low corporate taxes, capital and training grants, and the availability of plentiful supplies of cheap but educated labour. Up to the late 1980s, the branch plants set up under this policy tended to be heavily oriented to unskilled manufacturing assembly and packaging operations employing disproportionate numbers of women workers (Breathnach 1988(Breathnach , 1993. Ireland offered foreign rms a large latent reserve labour force arising from traditionally low female participation rates and strongly patriarchal social structures involving a high level of gender stereotyping in relation to education and employment, and a predominance of women in low-paying occupations (Barry 1998;O'Connor, 1998).…”
Section: N T E R N a T I O N A L B A C K O F F I C E D E V E L O P mentioning
confidence: 99%